Download presentation

Presentation is loading. Please wait.

Published byAutumn Kirk Modified over 2 years ago

1

2
Multiplying binomials You will have 20 seconds to answer each of the following multiplication problems. If you get hung up, go to the next problem when it appears, you will have time at the end to look back. A chime will sound when time expires and the next problem will appear. Click to begin

3
x(x – 4) #1

4
7(x + 3) #2

5
(x - 4)(x + 6) #3

6
(x + 5)(x + 3) #4

7
(x - 2)(x - 5) #5

8
(x + 7)(x - 2) #6

9
(x - 8)(x + 3) #7

10
(x + 5)(x + 7) #8

11
(x - 9)(x - 3) #9

12
(x - 4)(x + 4) #10

13
(x + 6)(x - 6) #11

14
(x - 5) 2 #12

15
(x + 5) 2 #13

16
You will have 25 seconds to answer the last 7 problems The chime will sound when the time has expired and the problem will change. Click to begin

17
(3x + 2)(x - 5) #14

18
(2x + 2)(3x + 1) #15

19
(4x - 5)(2x - 3) #16

20
(2x - 8)(3x + 4) #17

21
(2x - 6)(2x + 6) #18

22
(3x + 4) 2 #19

23
(3x - 4) 2 #20

24
Good job! If you need to go back and look over any problems, do so now. If not, relax a minute, then well check our answers to see how well we did. Click when youre ready to view the answers.

25
1. x(x – 4) = x 2 - 4x 2. 7(x + 3) = 7x (x - 4)(x + 6) = x 2 + 2x – (x + 5)(x + 3) = x 2 + 8x (x - 2)(x - 5) = x 2 - 7x (x + 7)(x - 2) = x 2 + 5x (x - 8)(x + 3) = x 2 - 5x (x + 5)(x + 7) = x x (x - 3)(x - 9) = x x (x - 4)(x + 4) = x Click to see remaining answers

26
11. (x + 6)(x - 6) = x 2 – (x – 5) 2 = x x (x + 5) 2 = x x (3x + 2)(x – 5) = 3x x (2x + 2)(3x + 1) = 6x 2 + 8x (4x – 5)(2x – 3) = 8x x (2x – 8)(3x + 4) = 6x 2 – 16x – (2x – 6)(2x + 6) = 4x 2 – (3x + 4) 2 = 9x x (3x – 4) 2 = 9x x + 16

Similar presentations

© 2016 SlidePlayer.com Inc.

All rights reserved.

Ads by Google